Analysis of Translation Techniques in "Me Before You" by Jojo Moyes - Vrisca Ananda Veruzia; Eva Nurul Candra; Tiarma Ika Yuliana (JEdu: Journal of English Education, 2023)
The purpose of this study is to identify and present the translation techniques used in the film Me Before You. The method in this research is descriptive qualitative, because the data presented is meaningful and can provide a real understanding. From the findings of the translation techniques in the film “Me Before You “founds as many as 446 data, the dominant translation techniques are Modulation as much as 90 data ( 20.2%), reduction 72 data (16.1%), literal translation 62 data ( 13.9%), compensation 46 data ( 10.3%), transposition 45 data ( 10.1%) Linguistics Compression 41 data ( 9,2%), Adaptation 11 data (2.5%), Calque 6 data (1,3%), Variation 3 data ( 0.7%), and Discursive Creation 1 data ( 0.2%).